Behavioural Aspects of Benchmark Quotation – the WIBOR Case - Mielus, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
In the post‑crisis environment, market indices are one of elements of the financial market which have to be reformed. The EU Regulation on indices used as benchmarks in financial instruments reflects a need for the reform of benchmark determination in order to make indices transparent, representative and resistant to manipulation. The reform changes the conduct of rate contributors (the so‑called panellists). The article analyses behavioural reactions of WIBOR panellists by indicating sources of the growth of inertia and the drop of dispersion of published benchmarks. Those reactions decrease the risk of banks and, at the same time, increase the divergence between an index and the actual cost of funds, which may threaten the stability of the financial market.